2020
DOI: 10.3390/polym12102418
|View full text |Cite
|
Sign up to set email alerts
|

Highly Scattering Hierarchical Porous Polymer Microspheres with a High-Refractive Index Inorganic Surface for a Soft-Focus Effect

Abstract: Functional light scattering materials have received considerable attention in various fields including cosmetics and optics. However, a conventional approach based on optically active inorganic materials requires considerable synthetic effort and complicated dispersion processes for special refractive materials. Here, we report a simple and effective fabrication strategy for highly scattering hierarchical porous polymer microspheres with a high-refractive index inorganic surface that mitigates the disadvantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…The excellent R̅ sun and the angle-independent reflectance can be ascribed to the hierarchical porous structure. First, the moderate porosity and the refractive index ( n ) difference between polymer matrix ( n ≈ 1.5) and air voids ( n = 1), together provide an efficient light scattering ability. , As a comparison, the dense poly­(TMPTA) coating has low R̅ sun of ∼0.09 (Figure S7a). Second, the continuous nano- to microscale pores ranging from ∼200 nm to ∼8 μm (Figure e), lead to multiple reflection via a dramatically prolonged dissipation route .…”
Section: Resultsmentioning
confidence: 99%
“…The excellent R̅ sun and the angle-independent reflectance can be ascribed to the hierarchical porous structure. First, the moderate porosity and the refractive index ( n ) difference between polymer matrix ( n ≈ 1.5) and air voids ( n = 1), together provide an efficient light scattering ability. , As a comparison, the dense poly­(TMPTA) coating has low R̅ sun of ∼0.09 (Figure S7a). Second, the continuous nano- to microscale pores ranging from ∼200 nm to ∼8 μm (Figure e), lead to multiple reflection via a dramatically prolonged dissipation route .…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the high specific surface area of the CSNs, the 140 nm SBT CSN-based paint showed the highest R% value. The NIR reflectance of the SBT CSNs can be attributed to the synergistic effects of their high specific surface area and porous nature and the difference in the refractive indices of the SiO 2 core and TiO 2 shell, which resulted in light reflection and scattering in the NIR region [ 18 , 45 ]. Previous studies have reported that the light reflectivity of core/shell or bilayered materials increases with an increase in the difference in the refractive indices of the constituent materials.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from particle sizes and the location of ZnO NPs laying on the surface or in the shell of ZPPs, the absorbance and absorption patterns of Pickering-like and hollow ZPPs are comparable. Multiple light scattering, between the high refractive index of ZnO NPs (1.9596) at the interface and the low refractive index of the PS core for Pickering-like ZPPs or the air void (1.0003) for hollow ZPPs, is possibly the major contributor for their shielding properties [ 48 ].…”
Section: Resultsmentioning
confidence: 99%